WEBVTT
00:00:00.000 --> 00:00:09.280
A point is moving on the curve of the function π of π₯ is equal to the square root of π₯ squared plus two.
00:00:09.710 --> 00:00:22.570
If its π₯-coordinate increases at a rate of nine square root of 15 centimeters per second, find the rate of change of the distance between this point and the point one, zero when π₯ is equal to three.
00:00:23.390 --> 00:00:30.450
The question tells us that a point is moving on the curve of the function π of π₯ is equal to the square root of π₯ squared plus two.
00:00:30.690 --> 00:00:37.890
It also tells us that its π₯-coordinate is increasing at a rate of nine square root of 15 centimeters every second.
00:00:38.450 --> 00:00:46.250
The question wants us to find the rate of change of the distance between this point and the point one, zero when π₯ is equal to three.
00:00:46.840 --> 00:00:55.830
Since the question wants us to find the rate of change of the distance between this point and the point one, zero, letβs calculate a formula for the distance between these two points.
00:00:56.310 --> 00:01:04.280
Since the point lies on the curve of the function π of π₯ is equal to the square root of π₯ squared plus two, its π¦-coordinate is going to be the output of this function.
00:01:04.800 --> 00:01:09.270
In other words, its Cartesian coordinates are π₯, square root of π₯ squared plus two.
00:01:09.780 --> 00:01:16.330
So we want to find an expression for the distance between the point one, zero and the point π₯, square root of π₯ squared plus two.
00:01:16.760 --> 00:01:21.430
We can do this by constructing a right-angled triangle and then using the Pythagorean theorem.
00:01:21.800 --> 00:01:31.240
Since weβre interested at the rate of change at the point when π₯ is equal to three, we see that π₯ is greater than one and the square root of π₯ squared plus two is greater than zero at this point.
00:01:31.240 --> 00:01:36.460
So weβll sketch the point π₯, square root of π₯ squared plus two up into the right of our point one, zero.
00:01:37.100 --> 00:01:42.000
We can then subtract the π₯-coordinates of these two points to find the base of our right-angled triangle.
00:01:42.080 --> 00:01:46.240
And we can subtract the π¦-coordinates to find the height of this right-angled triangle.
00:01:46.830 --> 00:01:52.060
This gives us a base of length π₯ minus one and a height of length square root of π₯ squared plus two.
00:01:52.510 --> 00:02:00.380
So by using the Pythagorean theorem, we have our distance squared is equal to π₯ minus one squared plus the square root of π₯ squared plus two squared.
00:02:00.910 --> 00:02:05.480
Distributing our exponent over the parentheses gives us π₯ squared minus two π₯ plus one.
00:02:05.740 --> 00:02:09.550
And the square root of π₯ squared plus two all squared is just π₯ squared plus two.
00:02:10.030 --> 00:02:14.710
We can simplify this further by adding our π₯ squared terms and adding our constants together.
00:02:14.960 --> 00:02:17.730
This gives us two π₯ squared minus two π₯ plus three.
00:02:18.130 --> 00:02:21.130
Finally, weβll take square roots of both sides of this equation.
00:02:21.520 --> 00:02:27.680
Since our distance is positive, this gives us that π· is equal to the square root of two π₯ squared minus two π₯ plus three.
00:02:28.090 --> 00:02:32.590
And so we found an equation for our distance function as a function of π₯.
00:02:32.940 --> 00:02:38.160
But the question wants us to find the rate of change of our distance with respect to time when π₯ is equal to three.
00:02:38.580 --> 00:02:42.170
But we have a function of π₯, so weβre going to have to apply the chain rule.
00:02:42.720 --> 00:02:50.740
The chain rule tells us if π¦ is some function of π’ and π’ is some function of π₯, then we can calculate the derivative of π¦ with respect to π₯.
00:02:50.740 --> 00:02:57.340
But first calculating the derivative of π¦ with respect to π’ and multiplying this by the derivative of π’ with respect to π₯.
00:02:57.950 --> 00:03:03.210
So by using the chain rule, we can calculate the derivative of our distance function with respect to time.
00:03:03.290 --> 00:03:10.680
But first calculating the derivative of our distance function with respect to π₯ and then multiplying this by the derivative of π₯ with respect to time.
00:03:11.330 --> 00:03:16.480
The question tells us the π₯-coordinate is increasing at a rate of nine root 15 centimeters per second.
00:03:16.510 --> 00:03:21.560
This is the same as saying the derivative of π₯ with respect to time is equal to nine root 15.
00:03:22.050 --> 00:03:24.370
So weβve already found dπ₯ by dπ‘.
00:03:24.410 --> 00:03:29.640
This means all we need to do now is find the derivative of our distance function with respect to π₯.
00:03:30.120 --> 00:03:37.170
So we need to calculate the derivative of two π₯ squared minus two π₯ plus three all raised to the power of a half with respect to π₯.
00:03:37.560 --> 00:03:43.130
Weβre now trying to differentiate the composition of two functions, so we can do this again by using the chain rule.
00:03:43.160 --> 00:03:51.360
If we set π’ equal to two π₯ squared minus two π₯ plus three, which is our inner function, then we have that π· is equal to π’ to the power of a half.
00:03:51.400 --> 00:03:53.590
But π’ is a function of π₯.
00:03:53.950 --> 00:04:06.430
So by using the chain rule, we can calculate the derivative of our distance function with respect to π₯ by first calculating the derivative of our distance function with respect to π’ and then multiplying this by the derivative of π’ with respect to π₯.
00:04:06.850 --> 00:04:13.950
To calculate the derivative of our distance function with respect to π’, we just need to calculate the derivative of π’ to the power of a half with respect to π’.
00:04:14.050 --> 00:04:16.860
We can do this by using the power rule for derivatives.
00:04:17.410 --> 00:04:21.020
We multiply by the exponent of a half and then reduce the exponent by one.
00:04:21.080 --> 00:04:23.840
This gives us a half π’ to the power of negative a half.
00:04:24.430 --> 00:04:31.610
Now, to calculate dπ’ by dπ₯, we need to differentiate π’ is equal to two π₯ squared minus two π₯ plus three with respect to π₯.
00:04:31.640 --> 00:04:33.900
Weβll again use the power rule for differentiation.
00:04:34.380 --> 00:04:39.630
The derivative of two π₯ squared is four π₯, and we subtract the derivative of two π₯, which is two.
00:04:39.660 --> 00:04:43.240
And finally, the derivative of the constant three is just equal to zero.
00:04:43.690 --> 00:04:48.230
Finally, weβll substitute π’ is equal to two π₯ squared minus two π₯ plus three.
00:04:48.750 --> 00:05:00.680
And then bringing our negative exponent down into the denominator gives us the derivative of our distance function with respect to π₯ is equal to four π₯ minus two divided by two multiplied by the square root of two π₯ squared minus two π₯ plus three.
00:05:01.100 --> 00:05:06.230
We are now ready to use the chain rule to find an expression for the derivative of our distance function with respect to time.
00:05:06.290 --> 00:05:13.750
Weβve calculated the derivative of our distance function with respect to π₯ and weβve calculated the derivative of π₯ with respect to π‘.
00:05:14.210 --> 00:05:26.180
This gives us the derivative of our distance function with respect to time is equal to four π₯ minus two multiplied by nine root 15 all divided by two multiplied by the square root of two π₯ squared minus two π₯ plus three.
00:05:26.580 --> 00:05:32.270
Finally, the question wants us to find the rate of change of our distance function with respect to time when π₯ is equal to three.
00:05:32.300 --> 00:05:35.410
So weβll substitute π₯ is equal to three into this expression.
00:05:35.860 --> 00:05:44.970
This gives us four times three minus two multiplied by nine root 15 all divided by two times the square root of two times three squared minus two times three plus three.
00:05:45.430 --> 00:05:52.400
We have that four times three minus two is 10, and we multiply this by nine root 15 to get a numerator of 90 square root of 15.
00:05:52.840 --> 00:05:58.030
Similarly, we can evaluate our denominator to get two multiplied by the square root of 15.
00:05:58.410 --> 00:06:03.710
So we have 90 root 15 divided by two root 15, which we can calculate to give us 45.
00:06:04.180 --> 00:06:09.730
And since the question tells us that these units are in centimeters per second, we can add units to this answer.
00:06:10.260 --> 00:06:18.600
Therefore, weβve shown that the rate of change of the distance between our point and the point one, zero when π₯ is equal to three is 45 centimeters per second.